Catalytic Alkynylation of Polyfluoroarenes by Amide Base Generated In Situ. Issue 44 (8th July 2019) - Shigeno, Masanori; Okawa, Takuya; Imamatsu, Masaya; Nozawa‐Kumada, Kanako; Kondo, Yoshinori
Abstract: We herein demonstrate that the amide base generated in situ from CsF and N(TMS)3 catalyzes the deprotonative coupling reactions of terminal alkynes with polyfluoroarenes, wherein mono‐ and dialkynylations occur efficiently for penta‐ and hexafluorobenzenes, respectively. Tetraalkynylated products could also be synthesized from dialkynylated compounds. Abstract : Aromatic substitution : Amide base generated in situ from CsF and N(TMS)3 catalyzes the deprotonative coupling reactions of terminal alkynes with polyfluoroarenes, wherein mono‐ and dialkynylations occur efficiently for penta‐ and hexafluorobenzenes, respectively. Tetraalkynylated products can also be synthesized from dialkynylated compounds (see scheme).